Faktor-Faktor Yang Berhubungan Dengan Keseimbangan Lansia Di Panti Tresna Werdha Inakaka, Kota Ambon - Valensya Yeslin Tomasoa; Joan Herly Herwawan (MOLUCCAS HEALTH JOURNAL, 2021)
The elderly experience a constant decline both physically and psychologically. Physical changes occur because of morphological changes in older muscles as you get older. Such physical changes cause slowing in motion, short steps, and muscle strength to drop and tend to wobble, resulting in slow aging in anticipation of the slipping, the tripping, the balance. Contributing factors include age, gender, body mass index (BMI) and physical activity. The purpose of this study is to identify factors related to the balance of the elderly in the house of tresna werdha inakaka, the city of ambon. This method of research is a descriptive description of a sectional cross. The sample sampling technique uses an purposive sampling of 49 respondents, with inclusions criteria: older people who can carry out their own activities and be willing to become the responders. Exact results of fisher's test are found with age relative to the balance of the elderly (p value= 0,000), there are genders with the elderly's balance (p value= 0,000), there are body mass indexes with the elderly's balance (p value= 0,000), and there is a relationship of physical activity with the elderly's balance (p value= 0,000).Key words: balance; Age; Gender; Body mass index; Physical activity